Pengaruh Latihan Square terhadap Daya Tahan Aerobic Atlet Sriwijaya Archery Club - Arisman Arisman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This research starts from the low endurance possessed by SAC athletes, therefore researchers are interested in exploring further and trying to contribute in the form of exercises namely square exercises to increase the aerobic endurance of athletes. This type of research was an experimental design with pretest-posttest control group design. The sample is 30 people. divided into two groups, namely (experimental group and control group, 15 people each). the experimental group was given treatment in the form of square exercise. The data collection technique is using the 12-minute run test with data analysis techniques using the t-test (different test). Based on the results of the study data analysis found tcount (11.12)> t table (1.75) and the value of sig. (p) 0,000 <of 0,05. Conclusion, square exercises can increase the aerobic endurance of athletes in the club's archery significantly. Keywords : Square Exercise, Aerobic Endurance